Penguatan Identitas Merek melalui Perancangan Logo dan Branding Digital untuk Meningkatkan Daya Saing UMKM di Wilayah Klipang, Kelurahan Sendangmulyo, Kota Semarang - Nana Noviada Kwartawaty; Albertus Setyo Sumargo; Glenda Angeli; Arisanti Ayu Wardhani; Ahmad Hafiyyan Shibghatalloh; Achmad Solechan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
This community service program aimed to strengthen the capacity of micro, small, and medium enterprises (MSMEs) in Klipang, Sendangmulyo, Semarang, in developing brand identity through logo design and digital branding. The program involved 30 MSME owners from various business sectors and adopted a participatory approach combined with Design Thinking. The activities were implemented in three stages: preparation, a three-day training program, and a week of mentoring. The program covered brand identity, brand value, logo design, brand story development, simple website development, Google Business Profile, and digital marketing. The results showed improvements across all indicators. The proportion of MSMEs with professional logos increased from 20% to 100%, consistent visual identity from 15% to 100%, brand story ownership from 5% to 100%, social media use for branding from 40% to 90%, and digital marketing understanding from 30% to 85%. Participant satisfaction reached at least 90%. These findings indicate that integrating Design Thinking, brand identity development, and digital branding is effective in strengthening MSME professionalism, product differentiation, and readiness to compete in the digital business environment.